The TanDEM-X Mission: Overview and Status - Zink, Manfred; Krieger, Gerhard; Fiedler, Hauke; Hajnsek, Irena; Moreira, Alberto; Werner, Marian (ENVISAT Symposium, 2007)
TanDEM-X opens a new era in space borne radar remote sensing. The first bistatic SAR mission, is formed by adding a second, almost identical spacecraft, to TerraSAR-X and flying the two satellites in a closely controlled formation with typical distances between 250 and 500 m. Primary mission objective is the generation of a consistent global digital elevation model with an unprecedented accuracy according to the HRTI-3 specifications. Beyond that, TanDEM-X provides a highly reconfigurable platform for the demonstration of new SAR techniques and applications. This paper gives an overview of the TanDEM-X mission concept, summarizes the capabilities of the system, illustrates the achievable performance, and provides some examples for new imaging modes and applications. The mission has been approved for full implementation by the German Space Agency with a planned launch in spring 2009. © 2007 IEEE.
DLR Import::2019-04-03
Keywords: Bistatic SAR formation; HRTI-3 DEM; New SAR techniques; Single-pass interferometry; TerraSAR-X